GAMES AS A MOTIVATING TOOL FOR SPORTS LEARNING (Fiep Bulletin - online, 2014)
In the literature, games have been pointed to be an educational instrument, since ancient Greece, by Plato, emphasized as content and teaching strategy by Comenius, Rousseau, Froebel, Montessori, Decroly and Dewey and, currently, as one of the main factors for human development (BRASIL.MEC, 1998; KISHIMOTO, 2001). However, for the potentialities of games to become effective, that is, for the children to learn, it is fundamental they have motivation, and an interest for the activity they perform (BECKER JÚNIOR, 1996; MURRAY, 1983). Therefore, the objectives of this field research are to analyze the children's perception as regards the use of games as a teaching strategy and to check if its practice motivates learning among children who belong to a sportive-social-educational project. The sample was composed of 338 children from 06 to 10 years old (46,95% of the population  720), who took part, at least, for a year, in 04 Nucleuses of the Rexona/Ades Volleyball Project in the State of Sao Paulo. The data were collected from a questionnaire on opinion scores, composed of three questions, on the perception of the practice of volleyball games adapted in the Project and through the implementation of a focal group with students. The Results demonstrate that, for the students, games make it easier (82%) and fun (88%) to learn and allow that all children play (83%), being indicated as the most enjoyable activity and a differential from other learning institutions and motivates the participation in the Project. Therefore, it can be verified that besides contributing to the full development of a child, they also are a motivational factor for learning, by establishing challenges, meanings, achievements and amusement to physical practices and awakening the desire to participate in activities, by fulfilling children's needs, thus its use becoming fundamental in sportive-educational classes, which aim at globally forming new citizens.
Keywords: Games; motivation; learning